Law Enforcement Against Illegal Investments - Muhamad Javier Ramzy; Upik Mutiara; Ronald Samuel Wuisan; Rijal Ibnu Sani (Jurnal Hukum Volkgeist, 2024)
nvestment is something that is growing rapidly in society. Apart from being easy, investing can also provide quite large profits. However, there is still a lot of illegal investment occurring in society. This is due to a lack of strict law enforcement and a lack of public education regarding investment. Therefore, it is necessary to educate the public and provide strict law enforcement to perpetrators of illegal investments so that people do not become victims in the future. Illegal investments usually offer large profits in a short time with low risk. Law enforcement against illegal investments can be carried out from two perspectives, namely civil and criminal. Investment is a rapidly growing trend within society, presenting an easy way to achieve substantial profits. Despite its potential benefits, there remains a significant presence of illegal investment activities. This issue primarily stems from insufficient law enforcement and a lack of public education about investment principles and risks. To mitigate this problem, it is crucial to enhance public awareness and implement stringent legal measures against those involved in illegal investments, ensuring that individuals are protected from becoming future victims. Typically, illegal investments promise high returns in a short period with minimal risk, attracting many unsuspecting individuals. Effective law enforcement against these fraudulent activities can be approached from both civil and criminal perspectives, addressing the issue comprehensively.